A modified symmetric local binary pattern for image features extraction - Majed O. Dwairi (Universitas Ahmad Dahlan, 2020)
The process of identifying images and patterns is one of the most important processes of digital image processing, which is used in many applications such as fingerprint recognition, face recognition and pattern recognition. Due to the large size of the image, the process of identifying the image requires a great time, which in turn leads us to extract some characteristics of the magnitude of the volume, which can be used as an identifier to retrieve the image or recognize it and thus we have devoted a lot of time to identify the image. In this research paper, a modified symmetric local binary pattern (MSLBP) method was proposed to extract texture features. The proposed algorithm was implemented on many digital fingerprint’s images and the local structure features of these images were obtained. Several image recognition experiments are conducted on these features and compared with other algorithms. The results of the proposed algorithm showed that the digital image was represented in a very small size and furthermore the speed and accuracy of image recognition based on the proposed method was increased significantly. Unlike the methods based on LBP, the proposed method gives the same features of the image even if the image was rotated with any angle.